An approach for computing the specific heat capacities of logs stored for a long time in an open warehouse. Issue 5 (3rd September 2022) - Deliiski, Nencho; Niemz, Peter; Angelski, Dimitar; Tumbarkova, Natalia
ABSTRACT: This paper describes an approach for computing the specific heat capacities of logs stored for long in an open warehouse. It includes the heat capacities of the wood of non-frozen and frozen zones in the logs and of both the frozen free and bound water in these zones, also the capacities formed by the release of the latent heat of both the free and bound water during their crystallization, as well as the effective specific heat capacities of logs stored in an open warehouse at periodically changing air temperature. The approach is based on the solutions of 2D models of the temperature distribution in logs during their alternating heating and cooling. Results from a simulative study of 2D unsteady temperature distribution and all types of the specific heat capacities of beech logs with a diameter of 0.4 m, length of 0.8 m, moisture content of 60%, and initial temperature of 0°C and 20°C during their 5 days and nights continous alternating heating, cooling, freezing and defrosting in an open warehouse at sinusoidal change of the ambient air temperature with various initial and different amplitudes in the range from –25°C to 40°C are graphically presented and analyzed.